Influencia de las constantes hidricas del suelo sobre la producción de alfalfa bajo riego - Sartor, Paolo Daniel; Masseroni, Maria Lujan; Sainz, Daiana Soledad; Aumassanne, Carolina Manuela; Fontanella, Dardo Roy; Zamora, Carlos Oscar; Alvarez, Cristian; Taboada, Miguel Angel (Asociación Argentina Ciencias del Suelo, 2023)
Poster y resumen